Students’ perception of using the RealLife English application for practicing English speaking skills - Najah Athirah; Ahmad Amin Dalimunte (Curricula: Journal of Curriculum Development, 2025)
Speaking is one of the most important skills for communication, but students still face a myriad of problems. This study explores students' perceptions of using RealLife English application for practicing English speaking skills. This study used a qualitative approach with a case study design. The participants in this study were ten eleventh-grade students from one of the high schools in Medan. Data were collected through observation and interviews during seven days of application usage. Data analysis was conducted using the thematic analysis method. The results showed that the use of the RealLife English application provided a positive perspective on the development of students' speaking skills. Students reported better confidence, speaking fluency, better pronunciation, and better vocabulary acquisition. Application features such as voice and video calls, podcasts, TV series, movies, and fire streak were highly influential in creating an interactive learning experience and encouraging consistency in practice. However, some technical challenges, such as internet network interruptions, annoying advertisements, and limited access to premium features, are obstacles faced by students. The implication of this study shows that the RealLife English application can be an alternative media for practicing students' speaking skills independently and flexibly.   Abstrak Berbicara merupakan salah satu kompetensi penting untuk berkomunikasi, namun segudang masalah masih banyak dihadapi siswa. Penelitian ini mengeksplorasi persepsi peserta didik dalam menggunakan aplikasi RealLife English dalam melatih kemampuan berbicara bahasa Inggris. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Partisipan dalam penelitian ini adalah sepuluh peserta didik kelas sebelas dari salah satu sekolah menengah atas di Medan. Data dikumpulkan melalui observasi dan wawancara selama tujuh hari penggunaan aplikasi. Hasil penelitian menunjukkan bahwa penggunaan aplikasi RealLife English memberikan perspektif positif terhadap perkembangan kemampuan berbicara peserta didik. Peserta didik mengalami peningkatan kepercayaan diri, kelancaran berbicara, pelafalan yang lebih baik, dan penguasaan kosakata yang lebih baik. Fitur-fitur aplikasi seperti panggilan suara dan video, podcast, serial TV dan film, dan fire streak sangat berpengaruh dalam menciptakan pengalaman belajar yang interaktif dan mendorong konsistensi dalam berlatih. Namun, beberapa tantangan teknis seperti gangguan jaringan internet, iklan yang mengganggu, dan keterbatasan akses ke fitur premium menjadi kendala yang dihadapi oleh peserta didik. Implikasi dari penelitian ini menunjukkan bahwa aplikasi RealLife English dapat menjadi media alternatif dalam melatih kemampuan berbicara peserta didik secara mandiri dan fleksibel. Kata Kunci: aplikasi seluler; kemampuan berbicara; pembelajaran mandiri; persepsi peserta didik